2018
DOI: 10.1017/s0266467418000093
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of leaf carbon (δ13C) and nitrogen (δ15N) of deciduous and evergreen understorey trees in two tropical Brazilian Atlantic forests

Abstract: Abstract:Isotopic composition of leaf carbon (δ13C) and nitrogen (δ15N) is determined by biotic and abiotic factors. In order to determine the influence of leaf habit and site on leaf δ13C and δ15N in the understorey of two Atlantic forests in Brazil that differ in annual precipitation (1200 and 1900 mm), we measured these isotopes in the shaded understorey of 38 tropical tree species (20 in the 1200-mm site and 18 in the 1900-mm site). Mean site values for δ15N were significantly lower at the 1200-mm site (−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 64 publications
2
21
1
Order By: Relevance
“…N availability in ecosystem, N re-translocation in plants, and N fractionation after plant uptake is known to influence leaf δ 15 N [1,41]. Multiple previous studies have reported that there is a positive relationship between plant δ 15 N and leaf N concentrations at various spatial scales [17]. In our work, leaf δ 15 N was also positively related to leaf N concentrations.…”
Section: Relationships Between the δ 13 C δ 15 N Values And Leaf Nutsupporting
confidence: 69%
See 3 more Smart Citations
“…N availability in ecosystem, N re-translocation in plants, and N fractionation after plant uptake is known to influence leaf δ 15 N [1,41]. Multiple previous studies have reported that there is a positive relationship between plant δ 15 N and leaf N concentrations at various spatial scales [17]. In our work, leaf δ 15 N was also positively related to leaf N concentrations.…”
Section: Relationships Between the δ 13 C δ 15 N Values And Leaf Nutsupporting
confidence: 69%
“…As a consequence of these effects, an enrichment of 13 C in current-year leaves was observed. During the autotrophic growth stage, carbon was assimilated and exported to other plant organs [17], which was most evident for older leaves [14]. The lighter carbon isotope was preferentially assimilated and used to produce the lipids and lignin, while the heavier carbon isotope was transported as 13 C-enriched sucrose to the young new leaves [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang et al [72] recognized that the δ 13 C of soil CO 2 emissions was negatively correlated with temperature after farmland was afforested in central China. According to Vitória et al [73], precipitation and δ 15 N values are negatively correlated until the point of soil waterlogging. Lee et al [71] suggested that changes of δ 13 C in SOM obviously follow those of the plant zone in arid and semiarid central East Asia.…”
Section: Temperature and Precipitationmentioning
confidence: 98%